2017
DOI: 10.1093/nutrit/nux001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary metabolites derived from gut microbiota: critical modulators of epigenetic changes in mammals

Abstract: The mammalian gastrointestinal tract harbors trillions of commensal microorganisms, collectively known as the microbiota. The microbiota is a critical source of environmental stimuli and, thus, has a tremendous impact on the health of the host. The microbes within the microbiota regulate homeostasis within the gut, and any alteration in their composition can lead to disorders that include inflammatory bowel disease, allergy, autoimmune disease, diabetes, mental disorders, and cancer. Hence, restoration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(115 citation statements)
references
References 106 publications
2
110
1
2
Order By: Relevance
“…It has also been demonstrated that reared fish show a different methylation pattern than that of their wild relatives (Le Luyer et al., ). As energetic and behavioral phenotypes are controlled by gut microbiota activity (Tremaroli & BĂ€ckhed, ) and the latter is suspected to impact epigenetic patterns (Bhat & Kapila, ; Cortese et al., ; Indrio et al., ; Rossi et al., ), our study is of prime interest as it is the first to demonstrate the extensive impact of captive rearing on gut microbiota composition in Atlantic salmon parrs meant for stocking. By identifying significant differences in terms of both structure and taxonomic composition between captive parrs and their wild relatives, the present work evidenced that acclimation to artificial rearing is also observable at the host–microbiota level.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has also been demonstrated that reared fish show a different methylation pattern than that of their wild relatives (Le Luyer et al., ). As energetic and behavioral phenotypes are controlled by gut microbiota activity (Tremaroli & BĂ€ckhed, ) and the latter is suspected to impact epigenetic patterns (Bhat & Kapila, ; Cortese et al., ; Indrio et al., ; Rossi et al., ), our study is of prime interest as it is the first to demonstrate the extensive impact of captive rearing on gut microbiota composition in Atlantic salmon parrs meant for stocking. By identifying significant differences in terms of both structure and taxonomic composition between captive parrs and their wild relatives, the present work evidenced that acclimation to artificial rearing is also observable at the host–microbiota level.…”
Section: Discussionmentioning
confidence: 90%
“…It has also been observed that gene regulation and hormone secretion of the host are affected by metabolites from bacterial activity acting as signal molecules (Tremaroli & BĂ€ckhed, ). Recent studies have also linked the microbiota composition with modification in epigenetic patterns in newborns, increasing the need to further investigate the role of the microbiota in the understanding of the phenotypic plasticity in teleosts (Bhat & Kapila, ; Cortese, Lu, Yu, Ruden, & Claud, ; Indrio et al., ; Rossi, Amaretti, & Raimondi, ). Because host–microbiota interactions are narrowly related to the host physiology (Donaldson et al., ; Klaasen et al., ; Liu et al., ; Scanlan et al., ; Wu & Lewis, ; Zhang, Lun, & Tsui, ), it is suspected that bacterial composition of microbial communities will tightly adapt to artificial rearing conditions (water composition, food, environmental bacterial community), which in turn will affect the ability of hatchery‐reared parrs to adapt to natural conditions once released.…”
Section: Introductionmentioning
confidence: 99%
“…The hMOs and NDCs investigated here do stimulate the development of the glycocalyx on intestinal epithelial cells. This may be a possible mechanism for the observed enhancing effects of hMOs and NDCs and its beneficial effects on gut microbiota that need the glycocalyx to adhere to the gut epithelium, with subsequent positive effects on fermentation products short chain fatty acids (SCFAs) and vitamins . Also, it may be a possible mechanistic explanation for the hMOs and NDCs induced enhanced gut barrier function .…”
Section: Discussionmentioning
confidence: 99%
“…The first is the capacity of gut microbes to induce a pro-carcinogenic inflammatory response [41][42][43]. The second is the production of secondary metabolites by gut microbes [44][45][46]. The ability of short chain fatty acids (SCFAs), hydrogen sulfide (H 2 S), secondary bile acids, and many other metabolites to impact the genome or epigenome of CECs, to alter rates of CRC progression, and to function as targets for CRC prevention or treatment is tremendously important and has thus been the topic of many recent reviews [47][48][49][50].…”
Section: Not Yet Identifiedmentioning
confidence: 99%